Delineating social entrepreneurship from related terminologies - Nigam, Shalini; Narang, Atul; Narang, Yogita (Journal of Entrepreneurship, Business and Economics; Vol 2 No 1 (2014), 2014)
Purpose- Social entrepreneurship is gaining ground rapidly as a field of research and practice and attracting increasing interest within the policy-making authorities, research on social entrepreneur-ship still falls far behind the practice. The different concepts used by the literature are often defined unwell and can take on a variety of meanings with little consensus so far reached among scholars. The concept of social entrepreneurship continues to convey different things to different people and there is no clear understanding and uniformity on where to locate it and on how to qualify social entrepreneurs. The paper is an attempt to clarify the boundary of Social Entrepreneurship and differ-entiating it from related concepts like: Corporate Entrepreneurship, sustainability and self-sufficiency, earned income strategies and social purpose businesses etc. Design/methodology/approach- To do so, secondary data had been used. The methodology involved the extensive use of Literature review in the field of Social Entrepreneurship. Findings- It can be said that definitions of social entrepreneurship and social enterprise vary to a great extent at the international level with a number of authors using the two interchangeably. The clarity has been provided in differentiating various related terms. Research Implications- There has been lot of confusions about to whom we can call social entrepre-neurs and what are the differences which make social entrepreneurs apart from their related commu-nities. More clarity on the concept will add to provide more ground for the expansion of social entrepreneurs. Originality/value- The present study is among the first study to clarify the similarities and differences in the field of Social Entrepreneurship and thus lays the foundation on which further research in the field of Social Entrepreneurship could be carried out. Research Paper Reference to this paper should be made as follows: Nigam, S., Narang, A., Narang, Y. (2014). ―De-lineating social entrepreneurship from related terminologies‖, Journal of Entrepreneurship, Business and Economics, Vol. 2, No. 1, pp. 1–20.